Komunikasi Profetik Dalam Mengajak Santri Non Mukim Mengaji Kitab: Studi Kasus di Pondok Pesantren Salafiyah Syafi’iyah Kabupaten Sorong, Papua Barat - Asikin, M. Azmi Hanan; Kahina, Dwi Iin; Suharmoko, Suharmoko (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
Communication has a very important role for human life, both in socializing and during the teaching and learning process. This study describes prophetic communication in Islamic boarding schools which aims to understand the process of prophetic communication in inviting non-mukim students to recite the Yellow Book. This study presents two substance problems, namely: 1) How is the implementation of prophetic communication in inviting non-mukim students to recite the Yellow Book at the Salafiyah Syafi'iyah Islamic Boarding School? 2) What are the obstacles in inviting non-mukim students to recite the Yellow Book? The above problems will be answered using qualitative research methods with an interview method approach. The data sources for this research were non-mukim students and ustadz/ustadzah at the Salafiah Syafi'iyah Islamic Boarding School. Furthermore, the data collection method used is observation, interviews, and documentation. The data obtained will be analyzed through data reduction, data presentation, and drawing conclusions. This study uses Kuntowijoyo's theory, the 3 pillars of prophetic communication. The results of this study indicate that prophetic communication is carried out by the Salafiah Syafi'iyah Islamic Boarding School. The implementation of prophetic communication is used in attracting non-mukim students to recite the Yellow Book, namely by communicating well (ma'ruf),